Periorbital Reconstruction With the Expanded Pedicled Forehead Flap. Issue 3 (March 2015) - Margulis, Alexander; Amar, Dalit; Billig, Allen; Adler, Neta
Abstract : Background: The complexity of structures within the periorbital region makes reconstruction of this area particularly a challenging endeavor. Within the literature, different techniques have been described for reconstruction of the external lamellae of the upper and lower eyelids as well as the medial and lateral canthal regions. Herein, we present the expanded pedicled forehead flap as a versatile and useful surgical option for reconstruction of various defects around the eye globe. Patients and Methods: A tissue expander is inserted underneath the forehead skin and serially expanded. The pedicle of the expanded pedicled flap is designed either from the superior portion of the expanded skin and interpolated to reconstruct the upper and lower eyelids, and the medial or lateral canthal areas; or from the inferior portion of the expanded skin and interpolated over the eyebrow to reconstruct the area between the upper eyelid crease and eyebrow. Fifteen patients with periorbital nevi or severe scarring were treated using the expanded forehead flap between the years 2003 and 2012. Thirteen patients had complex periorbital defects involving multiple anatomic areas, and 2 patients had defects confined to the upper eyelid area only. Results: Operative and postoperative course for 13 patients was uneventful. One patient had a late infection of the tissue expander but nonetheless continued with the reconstructive process. In 1 patient, the tissue expander was removed due to infection, and subsequent reconstruction was not carried out. The aesthetic and functional results of reconstruction were very good, and with excellent skin color and thickness match. In 1 patient, the flap was defattened in an ancillary procedure. No partial or complete flap loss was observed in this study. Summary: We conclude that the expanded pedicled forehead flap is a safe and reliable method for reconstruction of different segments of the periorbital region, while providing good aesthetic and functional reconstructive results with minimal donor-site morbidity.